Seismic anisotropy of the mantle lithosphere beneath the Swedish National Seismological Network (SNSN) - Eken, T.; Plomerová, J. (Jaroslava); Roberts, R.; Vecsey, L. (Luděk); Babuška, V. (Vladislav); Shomali, H.; Bodvarsson, R. (Tectonophysics, 2010)
Body-wave analysis – shear-wave splitting and P-travel time residuals - detect anisotropic structure of the upper mantle beneath the Swedish part of Fennoscandia. Geographic variations of both the splitting measurements and the P-residual spheres map regions of different fabrics of the mantle lithosphere. The fabric of individual mantle domains is internally consistent, usually with sudden changes at their boundaries. Distinct back-azimuth dependence of SKS splitting excludes single-layer anisotropy models with horizontal symmetry axes for the whole region. Based upon joint inversion of body-wave anisotropic parameters, we instead propose 3D selfconsistent anisotropic models of well-defined mantle lithosphere domains with differently oriented fabrics approximated by hexagonal aggregates with plunging symmetry axes.